Environmental Data Reader Bag for Hikers - Halid, Iffah Izati; Ahmed Mukred, Jameel Abdulla (Evolution in Electrical and Electronic Engineering, 2021)
Hiking is walking in nature and it is a natural exercise that promotes physical fitness that is economical and convenient since it requires no special equipment. Although hiking is a fun thing to do and becoming popular, but to be in a place that has a high altitude with a low temperature, pressure and high humidity still have a risk. In order to help the hikers know their limit when they go for hiking, the multisensory hiking bag for hiker is proposed. This hiking bag will be installed with the multisensory device which consists of two sensors, bmp180 and am2320 with the help of microcontroller board that have been programmed by Arduino Ide software. The multisensory device will show the reading of altitude, pressure, temperature and humidity on that place. Thus, this proposed multisensory hiking bag for hikers is believed to help the hiker know the environment around them to know their limit when go for hiking.